Rural development of regions of the Republic of Serbia in terms of employment and sources of income - Dimitrijevic, Miloš; Ristić, Lela; Despotović, Danijela (Anali Ekonomskog fakulteta u Subotici, 2021)
Integrated rural development enables linking agriculture with other economic activities whereby an adequate approach to regional development contributing to a more balanced development among regions. The aim of this research is to indicate that with the concept of integral rural development the differences between regions or rural and urban areas of Serbia could be reduced. Through the Kruskal-Wallis test for comparison of groups, the important differences were compared, where the results of research showed that they are very significant, especially between the Belgrade Region and the predominantly rural regions of Serbia. These differences can be overcome in rural areas if agriculture is more intensively linked with tertiary and secondary sectors.